Pengaruh Self-Agency Perempuan Pengolah Bakso Ikan Terhadap Tingkat Ketahanan Pangan Keluarga di Desa Muara, Kecamatan Wanasalam, Kabupaten Lebak - Shanty Kartika Dewi; Mahpudin Mahpudin; Wawan (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
In the view of feminism, women who are in a subordinate position have an influence on the formation of women's gender identity. This limits women in making decisions in their own lives. Thus, women become vulnerable to poverty, underdevelopment, and violence. Nevertheless, women fish ball processors in Muara Village, Wanasalam Sub-district, Lebak Regency are able to be empowered and choose to take on multiple roles. They become Self-Agencies as fish ball artisans motivated by economic factors. In the perspective of food security, income is one of the indicators that determine the level of household food security. This study examines the effect of Self-Agency of Women Fish Meatball Processors (X) on the Family Food Security Level (Y) in Muara Village, Wanasalam District, Lebak Regency. With a quantitative research method with a Guttman scale model and purposive sample technique. The results of the hypothesis test showed that there was an effect of Self-Agency of women fish ball processors on family food security by 25%. And the regression test results that the regression coefficient value of X is 0.351 (b) and the consistent value of the family food security variable is 14.521 (a). So that the conclusion obtained is that every additional 1% value of X value, the value of Y increases. Thus, the direction of the influence of X on Y is positive.